Murtadha Muthahhari: Filsafat Etika Islam - Naibin Naibin (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2020)
This paper discusses the thoughts of Murtadha Mutahhari about Islamic ethical philosophy. Philosophy of Islamic ethics is important to discuss as a comparison in the current discourse hegemony of Western ethics concepts. Western ethical concepts epistemologically pure concept of human, there is no role of religion and God. The concept of Western ethics has characteristics that ethics is the goal Islam has the basic ethics of religion and reason. Islamic ethics that ethics is a means "way" that introduces the spiritual nature of human to human intellectual and can assure religion. Data for this article with books, journals, and other sources relevant. Then the data were analyzed in accordance with article topics. This paper found that there are philosophical differences that underlie differences in ethical concepts western concept of Islamic ethics Murthadha Muthahhari. The concept of Islamic ethics is not an sich but out of criticism of the concept of ethics Muthahhari west. For a Muthahhari concept of Islamic Ethics in human means to know God. [Makalah ini membahas pemikiran Murtadha Mutahhari tentang filsafat etika Islam. Filsafat etika Islam penting untuk dibahas sebagai perbandingan dalam hegemoni wacana konsep etika Barat saat ini. Konsep etis Barat konsep manusia murni secara epistemologis, tidak ada peran agama dan Tuhan. Konsep etika Barat memiliki karakteristik bahwa etika adalah tujuan Islam memiliki etika dasar agama dan akal. Etika Islam bahwa etika adalah sarana "jalan" yang memperkenalkan sifat spiritual manusia ke intelektual manusia dan dapat meyakinkan agama. Data untuk artikel ini dengan buku, jurnal, dan sumber lain yang relevan. Kemudian data dianalisis sesuai dengan topik artikel. Makalah ini menemukan bahwa terdapat perbedaan filosofis yang mendasari perbedaan konsep etika dalam konsep barat etika Islam Murthadha Muthahhari. Konsep etika Islam bukan sich tetapi keluar dari kritik terhadap konsep etika Muthahhari barat. Untuk konsep Muthahhari tentang Etika Islam dalam manusia berarti mengenal Tuhan]